Analisis Nilai-nilai Religius dalam Novel "Janji Sahabat" Karya Risna Utami - Arni Lase; Mastawati Ndruru (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
Literary work is an expression of personal human feelings in the form of experiences, thoughts, feelings, ideas, enthusiasm, beliefs in the form of images of human life and the imagination of the author. One form of literary work is the novel "Promise of Friends" by Risna Utami. The researcher aims to analyze the religious values in the novel. The type of research used in this research is a type of qualitative research with a pragmatic approach. Analyzing the text in the novel "Promise of Friends" by Risna Utami, namely in the form of sentences, paragraphs and excerpts from dialogues of the characters in each paragraph which contain religious values. To complete the references in this study, the researchers carried out research at the Nias University library. Based on the results of the study, it can be concluded that Risna Utami's "Promise of Friends" novel contains religious values consisting of human relations with God, human relations with humans and human relations with nature which indirectly can be used as guidelines in daily life. -day. The researcher's suggestion is that the religious values contained in the novel "Promise of Friends" by Risna Utami can be applied and used as a guide in interacting life